2016
DOI: 10.24884/0042-4625-2016-175-6-33-37
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Changes of Colon Microbiocenosis in Patients With Colon Cancer

Abstract: Ключевые слова: рак толстой кишки, кишечная микро биота, дисбактериоз В в е д е н и е . В настоящее время трудно недооценить роль влияния кишечной микробиоты на организм человека. С развитием технологий в области молекулярной генетики значительно изменились представления о качественном и количественном составе микроорганизмов.По современным представлениям, абсолютное большинство (89%) в составе микробиоты здорового человека занимают микроорганизмы, относящиеся к двум крупным сообществам -бак тероидам (Bacteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
1
0
0
2
Order By: Relevance
“…Patients receiving autoprobiotics, compared to the control group, reported fewer postoperative complaints, as validated by the GIS for dyspepsia assessment and the GSRS for gastroenterological complaints. Improving the clinical data and stool frequency and form correspond to the results described when using probiotics by other authors in the treatment of oncological diseases [53,54]. Positive changes by the GSRS questionnaire in group A patients underscore the high efficacy of autoprobiotics in preventing postoperative stool disorders and dyspepsia in CRC patients.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Patients receiving autoprobiotics, compared to the control group, reported fewer postoperative complaints, as validated by the GIS for dyspepsia assessment and the GSRS for gastroenterological complaints. Improving the clinical data and stool frequency and form correspond to the results described when using probiotics by other authors in the treatment of oncological diseases [53,54]. Positive changes by the GSRS questionnaire in group A patients underscore the high efficacy of autoprobiotics in preventing postoperative stool disorders and dyspepsia in CRC patients.…”
Section: Discussionsupporting
confidence: 78%
“…Analysis of the frequency and consistency of stool before treatment showed that in patients with CRC with tumor localization in the left flank, there are stool disorders of both diarrhea (25% of patients) and constipation (25% of patients); in 50% of patients, there were no stool disorders. Analysis of the appearance of the first independent stool after surgery showed that individuals receiving an autoprobiotic had an independent stool of normal consistency (3-4 types on the Bristol scale) earlier than those who did not receive it (the stool was either 1-2 types, or 5-6 types on the Bristol scale [53,54]), and also against the background of rapid normalization of stool frequency, there was a low severity of flatulence in group A. Patients who took the treatment with autoprobiotics had a hospital stay of 5-7 days post-surgery, signifying the absence of postoperative complications.…”
Section: Clinical Datamentioning
confidence: 99%
“…Analysis of the appearance of the first independent stool after surgery showed that individuals receiving an autoprobiotic had an independent stool of normal consistency (3-4 types on the Bristol scale) earlier than those who did not receive it (the stool was either 1-2 types on the Bristol scale, or 5-6 types), and also against the background of rapid normalization of stool frequency, there were low severity of flatulence in group A. This corresponded to the results described when using probiotics by other authors in the treatment of oncological diseases [43,44].…”
Section: Clinical Datasupporting
confidence: 87%
“…По литературным данным, у всех пациентов с КРР возникают существенные сдвиги в кишечном микробиоценозе. Оперативное вмешательство с использованием антибактериальных препаратов приводит, как правило, к еще более тяжелым последствиям, проявляющимися в существенном изменении клинико-лабораторных показателей и состава микробиоты, которые создают предпосылки к таким серьезным осложнениям, как абдоминальный сепсис, псевдомембранозный колит, антибиотикоассоциированные дисбиозы и колиты [44][45][46].…”
Section: результаты исследования 1 клинико-лабораторные данныеunclassified